2019
DOI: 10.1002/cphc.201900853
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Modeling of Pressure‐Induced Spin Crossover in Octahedral Metal‐Ligand Complexes

Abstract: Spin state switching on external stimuli is a phenomenon with wide applicability, ranging from molecular electronics to gas activation in nanoporous frameworks. Here, we model the spin crossover as a function of the hydrostatic pressure in octahedrally coordinated transition metal centers by applying a field of effective nuclear forces that compress the molecule towards its centroid. For spin crossover in first-row transition metals coordinated by hydrogen, nitrogen, and carbon monoxide, we find the pressure r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 36 publications
(104 reference statements)
0
33
0
Order By: Relevance
“…In the future we plan to apply our methodology to a recently proposed mechanophore based on anthracene, [54] for which flex‐activation was tested but remained unsuccessful, with the aim of determining the optimal conditions (e. g. the pulling/deformation setup) for successful flex‐activation. Moreover, we plan to apply quantum mechanochemical models of pressure [55–58] to test the efficiency of flex‐activation in polymers, since experiments on flex‐activated mechanophores were performed under compression [24–26] . It will be insightful to juxtapose the influences of hydrostatic pressure and mechanical forces deforming the systems, which can be assumed to play a role in the process of flex‐activation.…”
Section: Methodsmentioning
confidence: 99%
“…In the future we plan to apply our methodology to a recently proposed mechanophore based on anthracene, [54] for which flex‐activation was tested but remained unsuccessful, with the aim of determining the optimal conditions (e. g. the pulling/deformation setup) for successful flex‐activation. Moreover, we plan to apply quantum mechanochemical models of pressure [55–58] to test the efficiency of flex‐activation in polymers, since experiments on flex‐activated mechanophores were performed under compression [24–26] . It will be insightful to juxtapose the influences of hydrostatic pressure and mechanical forces deforming the systems, which can be assumed to play a role in the process of flex‐activation.…”
Section: Methodsmentioning
confidence: 99%
“…In most cases, the octahedral ligand fields described in ref. [58] were found to be unproblematic in this regard.…”
Section: Hydrostatic Compression Force Fieldmentioning
confidence: 97%
“…However, it has been found that the pressure required for spin transition is a function of the position of the ligand in the spectrochemical sequence (cf. Table 1), [58,62] with strong field ligands requiring less pressure to induce spin crossover in the central metal ion, which paves the way for a rational design and precise tailoring of transition metal complexes that show spin transition at a desired pressure. Following up on this idea, it was possible to decrease the pressure required for spin transition by an order of magnitude by tuning the ligand field.…”
Section: Hydrostatic Compression Force Fieldmentioning
confidence: 99%
See 2 more Smart Citations